2017
DOI: 10.1016/j.compositesa.2017.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of randomly-oriented tow-based discontinuous composites and their equivalent laminates

Abstract: The equivalent laminate assumption is a commonly-used method to model the random architecture of discontinuous composites, but which has never been validated experimentally. This study aims to verify the equivalent laminate assumption, focusing on tow-based discontinuous composites (TBDCs), which have higher fibre-content and thus improved modulus and strength, compared to conventional discontinuous-fibre composites. This verification was achieved by manufacturing and testing (i) actual TBDCs with randomly ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 21 publications
(40 reference statements)
7
58
0
1
Order By: Relevance
“…In the literature, mechanical properties of TBDCs with different tow geometries and resin types have been measured. It has been found that the modulus of TBDCs generally falls between 40 and 50 GPa, whereas the tensile strength lies between 250 and 500 MPa [1,2,7,8]. In most studies, it has also been shown that, unlike conventional continuous-fibre composites, TBDCs have a slightly lower strength under tension than under compression [2,9].…”
Section: Operatorŝ Normalised Unit Vectormentioning
confidence: 99%
See 4 more Smart Citations
“…In the literature, mechanical properties of TBDCs with different tow geometries and resin types have been measured. It has been found that the modulus of TBDCs generally falls between 40 and 50 GPa, whereas the tensile strength lies between 250 and 500 MPa [1,2,7,8]. In most studies, it has also been shown that, unlike conventional continuous-fibre composites, TBDCs have a slightly lower strength under tension than under compression [2,9].…”
Section: Operatorŝ Normalised Unit Vectormentioning
confidence: 99%
“…It has been shown experimentally [7] that the equivalent laminate analogy is able to capture the failure mechanisms of TBDCs, although that study also highlighted the need to consider the intrinsic variability of the microstructure in TBDCs (which is not present in their equivalent laminates in order to predict their strength) [7].…”
Section: Operatorŝ Normalised Unit Vectormentioning
confidence: 99%
See 3 more Smart Citations